Recombinant fungal entomopathogen RNAi target insect gene. Issue 6 (1st November 2016) - Hu, Qiongbo; Wu, Wei
ABSTRACT: RNA interference (RNAi) technology is considered as an alternative for control of pests. However, RNAi has not been used in field conditions yet, since delivering exogenous ds/siRNA to target pests is very difficult. The laboratory methods of introducing the ds/siRNA into insects through feeding, micro feeding / dripping and injecting cannot be used in fields. Transgenic crop is perhaps the most effective application of RNAi for pest control, but it needs long-time basic researches in order to reduce the cost and evaluate the safety. Therefore, transgenic microbe is maybe a better choice. Entomopathogenic fungi generally invade the host insects through cuticle like chemical insecticides contact insect to control sucking sap pests. Isaria fumosorosea is a common fungal entomopathogen in whitefly, Bemisia tabaci . We constructed a recombinant strain of I. fumosorosea expressing specific dsRNA of whitefly's TLR7 gene. It could silence the TLR7 gene and improve the virulence against whitefly. Transgenic fungal entomopathogen has shown great potential to attain the application of RNAi technology for pests control in fields. In the future, the research interests should be focused on the selection of susceptible target pests and their vital genes, and optimizing the methods for screening genes and recombinants as well.